STATEMENT OF GEORGE B. DAVIS VICE-PRESIDENT, RESEARCH ENVIRONMENTAL AIR CONTROL, INC. HAGERSTOWN, MARYLAND 871203 - DAVIS, GEORGE (Tufts Archival Research Center, 2007)
Testimony from the vice-president of research of Environmental Air Control, Inc., (EACI) concerning the problem of air quality on airliner cabins. Cites three mechanisms to control measurement of environmental tobacco smoke and microbial concentrations on aircrafts including: ventilation, source control and filtration. States that research indicates that the third alternative, the HEPA (High Efficiency Particulate Air) filter, holds the greatest promise of improved airline quality, being both function effective and cost effective.